THE WONDER FOOD MUSEUM STORY: CELEBRATING MALAYSIA’S FOOD CULTURE AND CULINARY HERITAGE - ShawHong SER (E-Journal of Cultural Studies, 2020)
Although thematic museums centered around food culture and culinary heritage have beenaround for decades, the concept of food museum is still fairly new in Southeast Asia. Only in2015, the first food-oriented museum – “Wonder Food Museum” was established in Penang,Malaysia. Since its establishment, the museum has received positive feedback from bothlocal and international visitors. From 2017 to 2019, the museum has been selected as therecipient of the Certificate of Excellence by international well renowned Travel organization -TripAdvisor Inc. Meanwhile, the museum’s contribution to the state’s cultural and tourismdevelopment has also been recognized by the state authority. In 2017 and 2019, the museumwas awarded the ‘Top Museum Award (Unique Concept)’, and ‘Best Tourism(Museum)Award’ by the INPenang International Awards respectively. By and large, WonderFood Museum is currently one of the most outstanding museums in Malaysia and a wellknownattraction in Penang. In this paper, to response on the research scholarly interest inmuseum tourism in Southeast Asia, the researcher has made an attempt to document thedevelopment of Wonder Food Museum from 2015 to 2019. The museum’s curatorial concept,exhibits production, exhibition planning and its overall management will be discussed andanalyzed. As the aforementioned this paper will provide insights into an understanding of foodmuseum’s development in Malaysia. Keywords: Food museum, food culture, culinary heritage, Malaysia’s museum, museumtourism, interactive museum